Dialogue as a source of positive emotions during cross-border post-acquisition socio-cultural integration - Riikka Harikkala-Laihinen; Mélanie Hassett; Johanna Raitis; Niina Nummela (Emerald, 2022)
Purpose
The purpose of this paper is to analyse how dialogue can be used to promote post-acquisition socio-cultural integration. Specifically, it addresses questions regarding when and how companies can utilise dialogue to generate positivity regarding socio-cultural integration.
Design/methodology/approach
A single case study approach was adopted owing to its suitability for creating in-depth understanding in the context of socio-cultural integration. Primary data were collected via interviews, an employee satisfaction survey, and participant observation. Secondary data were obtained from the case company’s internal materials, such as strategies, integration workflows, and employee magazines. Analysis methods included descriptive statistics and thematic qualitative analysis.
Findings
The findings suggest that dialogue can be used to create positivity regarding socio-cultural integration throughout the stages of unfreezing, moving, and refreezing by actively engaging employees in voicing, listening, respecting, and suspending. It is proposed that cultural conflict during post-acquisition socio-cultural integration can be overcome through the generation of positivity; dialogue enables the collective management of emotions during post-acquisition integration by offering a platform for creating positivity and social cohesion; and due to its collaborative and engaging nature, dialogue provides an especially effective means of communication for overcoming cross-cultural conflict.
Originality/value
To the authors’ knowledge, this is the first attempt to showcase dialogue as a specific means of communication for creating positivity during cross-border socio-cultural integration. This study reached beyond comparative cultural research to offer views on positivity, emotion during socio-cultural integration, and dialogue as means for overcoming cross-cultural conflict.